Evaluation of Static Force Sense of Knee Flexor Muscles after the Reconstruction of the Anterior Cruciate Ligament: A Cross-Sectional Study - Mahmood Panahi; Sayed Mohsen Mirbod; Zahra Sadat Rezaeian (Vesnu Publications, 2019)
Introduction: The sense of force is one of the three main components of proprioception, associated with the realization of the force within the muscles during contraction. The purpose of this study was to investigate the static force sense of the knee flexor muscles after reconstruction of the anterior cruciate ligament (ACL) in comparison to healthy person's knee. Materials and Methods: This cross-sectional study was carried out on 32 non-athletic men aged 19-40 years who were assigned into two groups of 16 participants purposefully, ACL reconstruction and healthy. Using a Biodex machine 3.0, maximum voluntary isometric contraction of hamstring muscles was measured in 30°, 60°, and 90° angles in a random order. Then, 20% and 60% of maximum muscle contraction were calculated for each subject. The participants were requested to produce 20% and 60% contraction force randomly in aforementioned angles with and without visual feedback. This way the difference between subject' performance with and without visual feedback was calculated. The average of static force sense and the maximum voluntary isometric contraction (MVIC) were compared between the groups using Mann-Whitney U test. Using the Kendall's tau-b Correlation Coefficient, the correlation between MIVC and mean error of static force sense was determined. Results: There was no statistically significant difference between the groups in the term of average error of knee flexor static force sense in 30°, 60°, and 90° angles with target forces of 20% and 60% (P < 0.05). Moreover, the average error of flexor static force sense in 30°, 60°, and 90° angles and the maximum voluntary isometric contraction of knee flexor were not significantly correlated in either group (r ≤ 0.82, P > 0.05) Conclusion: It seems that the static force sense of knee flexor muscles of the knee will be similar to healthy subjects, 6 months after ACL reconstruction surgery.